A Survey-Based Study on Fashion Ateliers in Kuwait: Challenges and Opportunities - Al-Zamel, Mishari (Journal of Humanities and Social Sciences Studies, 2023)
This article investigates the loss and challenges of several Kuwaiti fashion ateliers. It also makes recommendations in an attempt to revitalize the business by providing insights into the issues and possibilities that these ateliers face across Kuwait. The research investigates the impact of historical events on high-street fashion enterprises and surveys fashion designers, supervisors, and female clients in Kuwait, drawing on international fashion background. That is, statistics on the impact of the coronavirus epidemic on local ateliers and female customer shopping behavior will be gathered. I hope that this study will heighten awareness about our local fashion studios and pave the way for initiatives that boost the industry's future.